PAKISTANI YOUTH AND THEIR CURRENT FINANCIAL NEEDS. DO WE HAVE A PLAN? - Rameez, Sahar; Tahir Abbasi (Journal of Pakistan Psychiatric Society, 2024)
Pakistan has been experiencing a financial crisis for several years, characterized by inflation and rising debt. These economic difficulties have had a significant impact on the country’s young, who make up a significant portion of the population. In addition, current political crises and inflation have exacerbated the situation, leading to an increase in adolescent mental health crises.